2002
DOI: 10.1051/0004-6361:20020351
|View full text |Cite
|
Sign up to set email alerts
|

An ISO and IUE study of planetary nebula NGC 2440

Abstract: Abstract. The infrared and ultraviolet spectra of planetary nebula NGC 2440 are presented. The observations were made by the Infrared Space Observatory (ISO) and the International Ultraviolet Explorer (IUE). These data, in conjunction with published optical observations have been used to derive electron temperature and density. The electron temperature increases with increasing ionization potential, from 11 000 to 18 000 K. The electron density has a constant value of 4500 cm −3 in agreement with previous dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…NGC 2440 has been observed by many authors, including Bernard-Salas et al (2002) who combined ISO IR data with IUE UV data and previously-published optical data; and Tsamis et al (2003), who observed the entire nebula and combined their optical data with IUE data; and Krabbe & Copetti (2006) observed in the optical only. Our ion-summed C abundance is 82% of what Tsamis et al (2003) reports, and only 28% of values reported by Kwitter et al (2003) and Bernard-Salas et al (2002). Our ion-summed N abundance is ∼50% of Kwitter et al (2003) Tsamis et al (2003).…”
Section: Ngc 2440contrasting
confidence: 45%
“…NGC 2440 has been observed by many authors, including Bernard-Salas et al (2002) who combined ISO IR data with IUE UV data and previously-published optical data; and Tsamis et al (2003), who observed the entire nebula and combined their optical data with IUE data; and Krabbe & Copetti (2006) observed in the optical only. Our ion-summed C abundance is 82% of what Tsamis et al (2003) reports, and only 28% of values reported by Kwitter et al (2003) and Bernard-Salas et al (2002). Our ion-summed N abundance is ∼50% of Kwitter et al (2003) Tsamis et al (2003).…”
Section: Ngc 2440contrasting
confidence: 45%
“…Lowering T e from 19,000 K to 15,000 K would double the Ne iii abundance derived from the 3869 8 line. It is known that in some PNs the temperature obtained from the Ne iii ion is lower than that from the O iii (Bernard-Salas et al 2002). Another possible explanation is that there are some regions with dust obscuring the optical emission lines.…”
Section: Neon and Sulfur Abundancesmentioning
confidence: 98%
“…Finally, we shall be presenting an Infrared Space Observatory (ISO) 1 pipeline spectrum for NGC 2440. Sections of these data have previously been presented by Bernard Salas et al (2002), and used to determine electron densities, temperatures and elemental abundances within the source. The basic characteristics of these observations can be summarized as follows.…”
Section: Observationsmentioning
confidence: 99%
“…This is not, however, the only possible explanation, or even the most likely. The ISO spectrum of the source has been analysed by Bernard Salas et al (2002), and we show a segment of these data in Fig. 5.…”
Section: Mid‐infrared Observations Of Planetary Nebulaementioning
confidence: 99%